Teacher Anxiety And Well-Being In Boarding Schools Of Kathmandu: A Desk Review - Dhungana, Ankita; Timalsina, Dhruba Prasad (Journal of Advanced Academic Research, 2025)
Boarding schools have organizational culture and policies that do not consider phenomenon of emotional labor experienced by teachers, and this place them as a high-risk group for developing stress and low job satisfaction. To ignore the obvious importance and interest of teachers’ mental health is not only taking a toll on teacher happiness and well-being, but it also has drastic consequences for the learning environment and hence learning outcome for students. The purpose of the desk review study is to analyse the anxiety and well-being of teachers in boarding schools respectively as per professional role, and personal role considering their impact on mental health. Applying Self-Determination Theory (SDT), this study provides a thematic analysis of literature, reports and institutional policy documents identifying role overload; professional identity conflicts, work-life balance, collegial support, and coping strategies. The results also revealed how role overload, ill-defined boundaries, and limited institutional support create a stressful climate that promotes burnout while collegial connections and coping support can foster teacher well-being. The study illustrated the potential of policy changes and institutions’ added support of teachers that could reduce stress and increase motivation and well-being, benefiting the teacher, the learning environment more broadly, and teacher well-being.